Discourse theory and the production of knowledge in democratic school management - Abdian, Graziela Zambão [UNESP]; Nascimento, Paulo Henrique Costa [UNESP]; Carvalho, Thamiris Slanzon de [UNESP]; Casagrande, Natalia [UNESP]; de Carvalho, Mônica Gomes [UNESP] (Universidade Estadual de Maringa, 2023)
Our objective is to analyze how Discourse Theory helps to constitute an effective theoretical-methodological reference for researchers in democratic school management that approaches the school as an empirical field. For this, we expose the historical context of research in educational administration/management and the construction of research that focuses on the school, identifying the elements that indicate a predominant mode in this subarea of Education; we explain the epistemological basis of Discourse Theory that can make operate a new analytical tools; we identified and analyzed publications in this subarea that worked with Discourse Theory and ended by exposing their contributions to the establishment of new relationships between the researcher and the school, enabling the advancement of knowledge.
La teoría del discurso y la producción de conocimiento en la gestión escolar democrática
Teoria do discurso e a produção do conhecimento em gestão escolar democrática
Keywords: democracy; discourse theory; poststructuralism; school management